Homophobia as Strategy: Nazi Persecution of Homosexuals and Today's Commemoration from a Gender-related Point of View (KULT_online, 2012)
This interdisciplinary volume deals with the historical research on the Nazi persecution of homosexuals and the different ways it regarded men and women. Authors writing in the disciplines of history, sociology, and art history take a closer look at the difficult process of commemoration as well as at retrospective homophobic stigmatization. The articles allow insight into current research on the persecution policies and analyse the myth of the 'gay Nazi', a still common explanation of Nazism. Considerations of the Berlin memorial to homosexuals persecuted under Nazism and its accompanying debates show today's problems of a symbolic commemoration, taking into account the question of gender-representation.